EFEKTIVITAS PROGRAM KARTU TANI PADA TATA KELOLA PENYALURAN PUPUK BERSUBSIDI DI KECAMATAN TINGGIMONCONG KABUPATEN GOWA - D, Arfin; Usman, Jaelan; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the effectiveness of the farmer card program on the governance of subsidized fertilizer distribution in Tinggimoncong District, Gowa Regency. This type of research is descriptive qualitative with data collection using observation, interview, and documentation techniques. Determination of informants using purposive sampling technique. The data validity technique used was source triangulation. The results showed that the amount of output that could be issued was effective because the e-RDKK system and based on the land area should not be more than 2 ha owned by farmers who run their farming businesses. The level of satisfaction obtained by most of the farmer card users is quite agree and satisfied with the existence of the farmer card program from the government. Creative products in this case are farmer cards and EDC machines in the distribution of subsidized fertilizers. The intensity that will be achieved during this farmer card process is related to the time of purchasing fertilizers that still use the old habits so that there is a buildup of buyers and causes delays in delivery, so far this goal still needs to be improved to achieve the goals of the farmer card program.